(untitled) (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Aim The purpose of this research is to study the formation of anti-inflammatory IL-4 cytokine and some indicators of moderate and severe preeclampsia, and normotensive pregnancies in the third trimester of pregnancy Material and methods This is a single center study of 100 women with third trimester pregnancies. All patients gave their informed consent prior to inclusion in the study.Patients were divided into two groups: 50 women with pregnancies complicated by varying degrees of preeclampsia and control group of 50 normotensive pregnancies. Cytokine levels in the serum were measured by the "sandwich" method of solid-phase enzyme immunoassay using double antibody. Statistical data processing was done using the SPSS13.0 software for Windows. Logistic regression analysis (Binary Logistic Regression) was used to determine the predictive role of the parameters analyzed in the occurrence of severe preeclampsia. Results The obtained values of Pearson- coefficients’ linear correlation (r) indicate that IL-4 negatively correlates with LDH, creatinine, uric acid and proteinuria, and positively correlates with number of blood platelets. IL-4 in severe preeclampsia has a downward trend, between 28-40 weeks of gestation it may be considered a prognostic marker for the development of severe preeclampsia